The Recycler's handbook (Berkeley, Calif. EarthWorks Press, 1990)
A handbook on how to recycle, reduce, and reuse many of the basic materials in our environment.
Includes bibliographical references (p. 127-130) and index.
Keywords: Conservation of natural resources; Environmental protection -- Citizen participation; Recycling (Waste, etc.); Salvage (Waste, etc.); Residuos Solidos E Limpeza Publica